Kondisi Kerja Fisik, Partisipasi Dalam Pengambilan Keputusan dan Kecemasan Sebagai Sumber Stres Pekerjaan Pada Guru Sekolah Negeri - Ekawarna, Ekawarna; Sofyan, Hendra (Makara Human Behavior Studies in Asia, 2010)
This research aims to analyze the direct and indirect effect of physical working conditions, participation in decision making and anxiety on the occupational stress of teachers. This research applies survey method. Structural equation modeling (SEM) is used to analyses the relationship of variables. There are 358 respondents, included 214 teachers from state primary schools, 88 teachers from state junior high schools, and 56 teachers from state senior high schools. Results show that there are direct negative and significant effect of the physical working conditions and participation in decision making to anxiety, direct positive and significant effect of anxiety to occupational stress, and indirect negative and significant effect of physical working conditions and participation in decision making to occupational stress through anxiety. These findings have an implication on the policy maker to give counseling, and training to assist all teachers in comprehending and recognizing the cause and impact of occupational stress.